The Study of the Contamination of the Paws of Dogs and Shoes with Eggs of Parasitic Nematodes - O. A. Panova; A. V. Khrustalev (Российский паразитологический журнал, 2020)
The purpose of the research devoted to the study of the possible factors of transmission of larval nematodosis pathogens, namely to clarify the possibility of nematodes eggs transfer from the soil to people’s homes on the dogs' paws and on people's shoes.Materials and methods. Three types of samples were examined for the presence of nematode eggs: the washings from the dog paws, from the shoes of dog owners, and the shoes of individuals that do not have pet dogs. To detect helminth eggs, the original protocol of the flotation-sedimentation method was used. A total of 150 volumetric samples were investigated.Results and discussion. In 17.3% of the samples from the paws of dogs and in 10.7% of the samples from the shoes of their owners, the eggs of parasitic nematodes were found. Toxocara eggs were found in 8.5% of samples, among them T. canis in 3.4%, T. cati in 5.1%; the eggs of Ancylostoma sp. in 2.5%, Trichuris cf. vulpis in 1.7%, Capillariidae gen. sp. in 2.5% of samples. In samples from the shoes of people who do not have dogs, nematode eggs were not found. All the eggs morphologically seemed to be alive. One third of the Toxocara eggs contained an embryo at the cleavage stage, the eggs of Trichuris and Capillariidae were at the zygote stage. Hookworm eggs contained larvae. The number of eggs found in the samples from the paws of dogs was almost double that on the shoes of their owners. Our study demonstrates that invasive parasitic agents can be carried from soil to human homes on shoe soles and dog paws. This fact needs to be accounted for when assessing the risk of worm infection in humans and dogs.